Prognostic impact and clinicopathological correlations of the cribriform pattern in pulmonary adenocarcinoma - Warth, Arne; Muley, Thomas; Kossakowski, Claudia; Stenzinger, Albrecht; Schirmacher, Peter; Dienemann, Hendrik; Weichert, Wilko (Journal of thoracic oncology, 2015)
A novel classification of pulmonary adenocarcinoma (ADC) distinguishing five growth patterns has been established by the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society. There is evidence that an additional cribriform pattern associates with a distinct clinical behavior. We evaluated the predominant growth pattern of 674 resected ADC as recommended by the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society, including the cribriform pattern. The predominant pattern type was correlated with clinical, molecular, and survival data. Two hundred forty-eight (36.8%) of the pulmonary ADC were solid, 207 (30.6%) were acinar, 101 (15%) were papillary, 55 (8.2%) were micropapillary, 35 (5.2%) were lepidic, and 28 cases (4.2%) were cribriform predominant (cpADC). Minor cribriform components were frequently observed (28.6% of all cases). cpADC showed the second highest proliferative capacity of all patterns, no somatic mutations in the epidermal growth factor receptor (p = 0.001) and a high rate of KRAS mutations. Overall survival (OS) of patients with cpADC (mean OS: 62.7 months) ranged in between survival times of patients with acinar (mean OS: 71.3 months) and solid predominant ADC (mean OS: 54.5 months); cpADC was associated with the worst disease-free survival (DFS) of all patterns (mean DFS: 36.9 months). Both associations were confirmed by multivariate analysis (p < 0.01 for both OS and DFS). Hazard ratios for cpADC were 1.72 for OS and 2.99 for DFS, with lepidic predominant ADC set as reference (hazard ratio: 1). Our data support the introduction of cpADC as a novel category into future morphology based on pulmonary ADC classifications. Further international studies are required to validate the reported clinicopathological associations of the cribriform pattern.